2017
DOI: 10.18388/abp.2017_1520
|View full text |Cite
|
Sign up to set email alerts
|

Fatty acid amide hydrolase (FAAH) inhibitor PF-3845 reduces viability, migration and invasiveness of human colon adenocarcinoma Colo-205 cell line: an in vitro study

Abstract: Earlier reports suggest that the endocannabinoids may play a role of endogenous tumor growth modulators. In this study, we investigated whether inhibition of the enzymes involved in the synthesis and degradation of endocannabinoids may reduce colorectal cancer cell invasion and migration. The human colon adenocarcinoma Colo-205 cells were incubated with PF-3845, JZL-184 and RHC-80267 (fatty acid amide hydrolase (FAAH), mono- (MAGL) and diacylglycerol lipase (DAGL) inhibitors, respectively) for 48 h. The MTT co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 39 publications
1
22
0
Order By: Relevance
“…Our detection of FAAH in MCF-7 (hormone sensitive), but not in MDA-MB-231 (hormone insensitive) cells, agrees with our findings in prostate cells with similar hormone sensitivity status [10]. This seems to be different in colon cancer cells as a study by Wasilewski et al [22] showed that inhibiting FAAH with a selective inhibitor (PF-3845) decreased the viability, migration and invasiveness of the Colo-205 cell line. In contrast, the similar efficacies of endocannabinoids in inhibiting proliferation of both BC cell types observed in our study, irrespective of their high or low FAAH expression, suggested the enzyme was perhaps unimportant in this process or that sufficient endocannabinoid was always present in our in vitro system irrespective of FAAH activity.…”
Section: Discussionsupporting
confidence: 90%
“…Our detection of FAAH in MCF-7 (hormone sensitive), but not in MDA-MB-231 (hormone insensitive) cells, agrees with our findings in prostate cells with similar hormone sensitivity status [10]. This seems to be different in colon cancer cells as a study by Wasilewski et al [22] showed that inhibiting FAAH with a selective inhibitor (PF-3845) decreased the viability, migration and invasiveness of the Colo-205 cell line. In contrast, the similar efficacies of endocannabinoids in inhibiting proliferation of both BC cell types observed in our study, irrespective of their high or low FAAH expression, suggested the enzyme was perhaps unimportant in this process or that sufficient endocannabinoid was always present in our in vitro system irrespective of FAAH activity.…”
Section: Discussionsupporting
confidence: 90%
“…() postulated that the antiproliferative activity of AEA may be due to the reduction of polyamine levels that play a critical role in cell proliferation. Finally, the inhibition of FAAH also reduced the viability, migration and invasion of Colo‐205 cells in vitro (Wasilewski et al, ).…”
Section: Endocannabinoid Antitumour Activitymentioning
confidence: 99%
“…Ammonium supplementation to glutamine-containing culture media was able to stimulate growth of the highly malignant HeLa, MDA-MB-231, PC3, HCT116, and Colo205 cancer cells in 2-D cultures. These human cancer cell lines are metastatic and hence have heightened abilities for migration, invasion, and colonization in glutamine-containing media (51)(52)(53)(54)(55)(56). They also show enhanced drug resistance due to overexpression of plasma membrane multidrug pumping ATPases, including P-glycoprotein and multidrug resistance protein-1 (57).…”
Section: Ammonium Promotes Metastatic Cancer Cell Proliferationmentioning
confidence: 99%
“…Cell growth was followed by counting cellular density every 24 h during 7 to 8 days. Viability was determined by the trypan blue assay, which revealed <10% cellular death (54). The duplication time was determined by using the following equation:…”
Section: Cell Growth and Culturementioning
confidence: 99%